Avaliação clínica e microbiológica do tratamento da estomatite protética com tintura de Schinus terebinthifolius Raddi (Aroeira) - Soares, Diana Gabriela de Sousa [UNESP]; de Oliveira, Cibele Braga [UNESP]; Paulo, Marçal de Queiroz; Carvalho, Maria de Fátma Farias Peixoto; Padilha, Wilton Wilney Nascimento (APESB (Associacao de Apoio a Pesquisa em Saude Bucal), 2010)
Objective: To evaluate the clinical efficacy of Schinus terebinthifolius Raddi (aroeira) tincture in the treatment of denture stomatitis. Method: Eighteen removable denture wearers with clinical diagnosis of type II denture stomatts and presence of candidosis associated to the denture use, as confirmed by clinical and mycological examinations, were selected for the study. The patients were allocated to two groups: TG (test group) - treatment with Schinus terebinthifolius Raddi (aroeira) tincture; CG (control group), treatment with nystatin. All patients were instructed to clean the dentures with toothbrush and dentifrice, and then apply the product on the palatal mucosa and on denture surface 3 times a day, during 15 consecutive days, removing the denture at bedtime and keeping it in a receptacle with water. At the 15th day of use, the clinical and mycological examinations were redone to evaluate treatment efficacy. Data were analyzed statistically by Wilcoxon and Mann-Whitney tests at 5% significance level. Results: The inflammatory process and Candida spp. infect on were eliminated in 66.7% and 77.8% of the cases, respectively, in TG. In CG, elimination of the inflammatory process and fungal infect on occurred in 77.8% and 88.9% of the cases, respectively. These results were statistically significant (p=0.01). There was no statistically significant difference between the treatments (p>0.05). In all cases, fungal infect on was detected only on the denture, and C. albicans was the most prevalent microorganism, being present in 94.4% of the cases. Conclusion: The treatment with Schinus terebinthifolius Raddi (aroeira) tincture was effective in the treatment of denture stomatitis, promoting remission of the inflammatory process and Candida spp infection.
Clinical and microbiological evaluation of the treatment of denture stomatitis with Schinus terebinthifolius Raddi (Aroeira) tincture
Keywords: Candida; Clinical trial; Denture; Stomatitis